Environmental education as a remedying source between human interference and the Nisia Floresta Flona (Research, Society and Development, 2021)
The occupation of areas surrounding Conservation Units should not jeopardize the priority of conservation objectives. To guarantee this priority, it is necessary to reconcile the use of natural resources and the conservation of the area. In this context, Environmental Education tools can help to maintain the sustainable use of these areas. The objective was to initiate an Environmental Education work with the surrounding residents of the Conservation Unit, revealing its importance and how society can interact and promote ways for local environmental awareness, respecting the collective characteristics and showing how much their participation is essential and effective for long-term success in the conservation. The environmental perception of the residents of the community surrounding the Unit was evaluated, which is located in the Bonfim / Guaraíra Environmental Protection Area and a survey of socioenvironmental data was carried out through questionnaires and technical visits together with the carrying out of an action of environmental education. Through the analysis of the obtained data, it was contacted the lack of knowledge of the residents about basic concepts about the Environment and that many are still unaware of the National Forest Conservation Unit of Nísia Floresta. Educational activities were carried out. In this way, it was understood how much the environmental perception is an important instrument to intercept the interaction of the communities that live around the Conservation Units and that it must be widely used as an assessment tool.